Multi-locus deletion mutation induced by silver nanoparticles: Role of lysosomal-autophagy dysfunction - Bo Si; Xue Wang; Yun Liu; Juan Wang; Yemian Zhou; Yaguang Nie; An Xu (Ecotoxicology and Environmental Safety, 2023)
Due to the rapid production growth and a wide range of applications, safety concerns are being raised about the genotoxic properties of silver nanoparticles (AgNPs). In this research, we found AgNPs induced a size-dependent genotoxicity via lysosomal-autophagy dysfunction in human-hamster hybrid (AL) cells. Compared with 25 nm and 75 nm particles, 5 nm AgNPs could accentuate the genotoxic responses, including DNA double-strand breaks (DSBs) and multi-locus deletion mutation, which could be significantly enhanced by autophagy inhibitors 3-methyl adenine (3-MA), Bafilomycin A1 (BFA), and cathepsin inhibitors, respectively. The autophagy dysfunction was closely related to the accumulation of 5 nm AgNPs in the lysosomes and the interruption of lysosome-autophagosome fusion. With lysosomal protective agent 3-O-Methylsphingomyelin (3-O-M) and endocytosis inhibitor wortmannin, the reactivation of lysosomal function and the recovery of autophagy significantly attenuated AgNP-induced genotoxicity. Our data provide clear evidence to illustrate the role of subcellular targets in the genotoxicity of AgNPs in mammalian cells, which laid the basis for better understanding the health risk of AgNPs and their related products.